Dampak Pemikiran Tauhid Muhammad Bin Abdul Wahhab Dan Abul Hasan Al-Asy'ari Terhadap Dakwah Kontemporer - Setiana, Unang; Zouhrotunni'mah, Zouhrotunni'mah; Yono, Yono (Universitas Ibn Khaldun Bogor, 2018)
Tawhid da'wah is the main mission of the Prophets and Apostles sent by Allah SWT. Muhammad bin Abdul Wahhab and Abul Hasan al-Asy'ari are influential figures in the hazanah of tauhid thinking. His thoughts spread throughout the world and many were followed by Muslims. This led to a number of differences in istinbath a problem and caused his followers to form a firqah that defended the founders of Manhaj. In this study wanted to find out how Muhammad bin Abdul Wahhab and Abul Hasan al-Asy'ari's views on asthma wa traits, and know how the impact of Muhammad bin Abdul Wahhab and Abul Hasan al-Asy'ari's thoughts on contemporary da'wah. This research is a library research study. From the results of the study it appears that Muhammad bin Abdul Wahhab's view of asthma wa is the character of what Allah and His Messenger have set in the Qur'an and hadith. Asma wa traits are part of ushul iman, tauqifiyah cases, without takyif (asking how), tasybih (liking), takwil (changing meaning). Whereas Abul Hasan al-Asy'ari's view is to believe in asthma wa traits in accordance with the Qur'an and sunnah with no resemblance to His creatures (tajsim/tasybih). The impact of his thoughts on contemporary da'wah is the division of three groups of tauhid voters, namely: the wahhabiyah/salafiyah group, the al-Asya'iroh group, and the group that benefits from the two.